A Cost Estimation for CO2 Reduction and Reuse by Methanation from Cement Industry Sources in Switzerland - Baier, Jens; Schneider, Gabriel; Heel, Andre (Frontiers in Energy Research, 2018)
The Swiss government has signed the Paris Climate Agreement and various measures need to be implemented in order to reach the target of a 50% reduction in CO2 emissions in Switzerland by 2030 compared with the value for 1990. Considering the fact that the production of cement in Switzerland accounts around 2.5 million ton for CO2 emissions of which corresponds to roughly 7% of the country’s total CO2 emissions, the following article examines how this amount could be put to meaningful use in order to create a new value-added chain through CO2 methanation, and thus reduce the consumption and import of fossil fuels in Switzerland. With power-to-gas technology, this CO2, along with regenerative hydrogen from photovoltaics, can be converted into methane, which can then be fed into the existing natural-gas grid. This economic case study shows a cost prediction for conversion of all the CO2 from the cement industry into methane by using the technologies available today in order to replacing fossil methane imports.